Desorption of bisphenol A from microplastics under simulated gastrointestinal conditions - Li, Wang; Zu, Bo; Li, Lei; Li, Jian; Li, Jiawen; Mei, Xueyu (Frontiers in Marine Science, 2023)
Microplastics are prevalent in the environment and have a strong affinity to pollutants owing to their large specific surface area and hydrophobicity. Once ingested, microplastics transport pollutants into organisms. This study investigated bisphenol A (BPA) desorption behavior from three microplastic materials, namely, polystyrene (PS), polypropylene (PP), and polyamide (PA), under simulated biological gastrointestinal conditions. The results showed that BPA can rapidly desorb from microplastic carriers under simulated gastrointestinal conditions, with different BPA desorption percentages in the order of PP > PS > PA. This was related to the amorphous structure and functional groups of the polymers. The BPA desorption behavior of microplastics in gastric juices was not significantly affected by pH; however, within the pH range of intestinal juices, the BPA desorption percentage increased significantly as the pH increased. The increase in Na+ concentration in the gastrointestinal tract exhibited a certain inhibitory effect on BPA desorption from microplastics owing to the salting-out effect. The temperature of digestive juices positively affected BPA desorption, suggesting that endothermic organisms are more susceptible to it. Our findings help elucidate the potential health risks of exposure to microplastics and their sorbed pollutants in the environment.